Frequency of Thyroid Function Abnormalities among Patients of Type II Diabetes Mellitus - Dolat Singh, Ihsanullah Rajar, Rajkumar, Ayaz Ahmed, Priya Kumari Maheshwari, Majida Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of thyroid function changes in type II Diabetes mellitus patients Material and methods: This cross-sectional study was carried out at the Medicine OPD of Indus Medical College Tando Muhammad Khan. The study duration was six months, from December 2020 to May 2021. All the diagnosed cases of type 2 diabetes mellitus, aged 40 to 65 years and both genders were included. Each case underwent a 5 ml blood sample, which was sent immediately to the diagnostic laboratory of the hospital to assess the TSH level for thyroid function. The research proforma was applied to gather all the data, and SPSS software version 26 was utilized to analyse the results. Results: A total of 200 diabetic patients were studied; their average age was 46.23+7.11 years. Females were in the majority 60.0%. The overall average of HbA1c was 7.02+1.41%. Out of all the hypothyroidism cases were 6.5% and hyperthyroidism cases were 2.5%, while in 90.0% of the cases, thyroid stimulating hormone (TSH) was normal. Thyroid function abnormalities were statistically insignificant according to gender (p-993). Conclusion: As per the study conclusion, thyroid function abnormalities were observed to be 9% among patients of type II diabetes mellitus. Keywords: Diabetes, Type II, thyroid function, HBA1C